Biallelic Variants in OTUD6B Cause an Intellectual Disability Syndrome Associated with Seizures and Dysmorphic Features - Santiago-Sim, Teresa; Burrage, Lindsay C.; Ebstein, Frédéric; Tokita, Mari J.; Miller, Marcus; Bi, Weimin; Braxton, Alicia A.; Rosenfeld, Jill A.; Shahrour, Maher; Lehmann, Andrea; Cogné, Benjamin; Küry, Sébastien; et al. (American journal of human genetics, 2017)
Ubiquitination is a posttranslational modification that regulates many cellular processes including protein degradation, intracellular trafficking, cell signaling, and protein-protein interactions. Deubiquitinating enzymes (DUBs), which reverse the process of ubiquitination, are important regulators of the ubiquitin system. OTUD6B encodes a member of the ovarian tumor domain (OTU)-containing subfamily of deubiquitinating enzymes. Herein, we report biallelic pathogenic variants in OTUD6B in 12 individuals from 6 independent families with an intellectual disability syndrome associated with seizures and dysmorphic features. In subjects with predicted loss-of-function alleles, additional features include global developmental delay, microcephaly, absent speech, hypotonia, growth retardation with prenatal onset, feeding difficulties, structural brain abnormalities, congenital malformations including congenital heart disease, and musculoskeletal features. Homozygous Otud6b knockout mice were subviable, smaller in size, and had congenital heart defects, consistent with the severity of loss-of-function variants in humans. Analysis of peripheral blood mononuclear cells from an affected subject showed reduced incorporation of 19S subunits into 26S proteasomes, decreased chymotrypsin-like activity, and accumulation of ubiquitin-protein conjugates. Our findings suggest a role for OTUD6B in proteasome function, establish that defective OTUD6B function underlies a multisystemic human disorder, and provide additional evidence for the emerging relationship between the ubiquitin system and human disease.